Poules et poulets entre métaphores et realia dans la prédication et les exempla du Moyen Âge - Marie Anne Polo de Beaulieu (Revue d'ethnoécologie)
Thanks to a chosen corpus of sermons and exempla from the 13th century to the 15th century, we will be able to catch the imaginary linked to the hen, to compare it with other birds, to observe its setting in a social context near to realia. These texts also shed a light on its place in the moralized naturalist knowledge, inspired by Bestiaries and finally the extreme allegorization of the hen and the kitchen used to represent Virgin Mary, the Christ or even God, in some sermons and exempla.